The Evolutionary Properties on Solitary Solutions of Nonlinear Evolution Equations - Wenxia Chen; Danping Ding; Xiaoyan Deng; Gang Xu (Advances in Mathematical Physics)
The evolution process of four class soliton solutions is investigated by basic calculus theory. For any given x, we describe the special curvature evolution following time t for the curve of soliton solution and also study the fluctuation of solution curve.